Sweet Virginia [videorecording (DVD)] - Bernthal, Jon; Abbott, Christopher, 1986-; Poots, Imogen, 1989- (Shout! Factory, 2018)
A mysterious stranger sends shockwaves through a close-knit community in this nerve-jangling slice of raw suspense. In the wake of a triple murder that leaves the residents of a remote Alaskan outpost on edge, tightly wound drifter Elwood checks into a motel run by Sam, a former rodeo champion whose imposing physical presence conceals a troubled soul.